4 - African ‘Youth’ since Independence: Notes on a Bibliographic Overview, 1990–2005: by Fiona Klein Klouwenberg & Inge Butter - Klouwenberg, Fiona Klein; Butter, Inge (Africa Development, 2021)
This short bibliography on ‘youth’ is the result of a literature search carried out in 2005 in three library collections in the Netherlands. The references to the general literature on youth, politics and religion were found in the library of the Faculty of Social and Behavioural Sciences of Leiden University. For African references on this topic, the library of the African Studies Centre in Leiden was very useful. The Royal Tropi- cal Institute’s library in Amsterdam was also used but to a lesser extent. The keywords used for the literature search were ‘youth’, ‘politics’ and ‘religion’ in four different languages: English, French, German and Dutch. This resulted in 270 references addressing the specific topics of youth, politics and religion, which all fall within the scope of the conference.